Modern power system analysis - Kothari, D. P. (Dwarkadas Pralhaddas), 1944-; Nagrath, I. J. (Tata McGraw-Hill Education Private Limited, 2011)
The book provides for an in-depth study of power systems analysis, power systems stability, and powersystems operation and control courses as offered at the undergraduate level across indian universities.the rich and robust content caters to the requirements of a related postgraduate course and will alsogreatly benefit practicing engineers.